Comparison of Immunological and Virological Recovery with Rapid, Early, and Late Start of Antiretroviral Treatment in Naive Plwh Real-World Data - Yildirim, Figen Sarigul; Candevir, Aslihan; Akhan, Sila; Kaya, Selcuk; Cabalak, Mehmet; Ersoz, Gulden; Celen, Mustafa Kemal (Dove Medical Press Ltd, 2023)
Background: Rapid initiation of antiretroviral therapy (ART) reduces the transmission of HIV infection in the community. This study aimed to determine whether rapid ART initiation is effective compared to standard ART treatment in our country. Methods: Patients were grouped based on time to treatment initiation. HIV RNA levels, CD+4 T cell count, CD4/CD8 ratio, and ART regimens were recorded at baseline and follow-up visits for 12 months. Results: There were 368-ART naive adults (treatment initiated at the time of HIV diagnosis; 143 on the first day, 48 on the secondseventh day, and 177 after the seventh day). Although virological suppression rates at 12th months were higher in all groups, over 90% on average, there were no statistically significant differences in HIV-1 RNA suppression rates, CD+4 T cell count, and CD4/CD8 ratio normalization in the studied months but in multivariate logistic regression analysis; showed a significant correlation between both virological and immunological response and those with CD4+ T <350 cells/mL at 12th month in total patients. Conclusion: Our findings support the broader application of recommendations for rapid ART initiation in HIV patients.
Keywords: HIV; ART; antiretroviral; rapid start